Undergraduates' personal circumstances, expectations and reasons for attending university. Issue 8 (3rd August 2017) - Balloo, Kieran; Pauli, Regina; Worrell, Marcia
Abstract : Undergraduate students are likely to have a range of reasons for attending university and expectations about their education. The current study aimed to determine the most prevalent reasons and expectations among students, and how these differed based on their personal circumstances. First-year undergraduate psychology students completed a questionnaire on reasons for attending university and expectations of university regarding assessment, teaching, learning and organisational resources. Improving career prospects was found to be the most important reason for attending university. The most important aspect of assessment was receiving feedback clarifying things they did not understand. Being good at explaining things was the most important teaching quality. Reasons and expectations were also found to differ depending on students' gender, age group, caring responsibilities, application route, fee status and whether English is their first language. Implications for educators are discussed in terms of bringing student experiences more in-line with their expectations.